Malaysian intangible heritage asset Mak Yong and Dondang Sayang: the financial disclosure viewpoint / Amrizah Kamaluddin , Mohamad Hafiz Rosli and Memiyanty Abdul Rahim - Kamaluddin, Amrizah; Rosli, Mohamad Hafiz; Abdul Rahim, Memiyanty (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Intangible Heritage Assets (HA) are significant to a country's culture and traditions and serve as symbols of civilizations. They hold importance not only for society but also from an economic perspective. UNESCO began recognizing intangible cultural heritage in 2003. In Malaysia, performing arts such as Mak Yong and Dondang Sayang have been recognized by UNESCO as part of the world's intangible cultural heritage. Furthermore, these performance arts have become a draw for visitors to Malacca and Kelantan, Malaysia. Developed countries such as Australia, New Zealand, and the United Kingdom have reported on HAs. However, the current accounting standard, IPSAS 31 Intangible Assets, offers limited guidelines for reporting on these assets, making it crucial to address this issue given the fragility of such assets. The objectives of this study are to explore the perceptions of performing arts experts on accounting for the intangible HAs Mak Yong and Dondang Sayang and to identify the components of intangible HAs that should be reported. A qualitative case study approach was applied, utilizing in-depth face-to-face interviews with performing arts experts of Mak Yong and Dondang Sayang to comprehensively understand their views on accounting for intangible HAs, particularly in relation to performing arts. The findings reveal that descriptive information, including the costs associated with the performing arts and significant and captivating details about intangible HAs, should be disclosed in the notes to the accounts or in supplementary documents to public sector reports to highlight these valuable assets. The study's findings offer insights into public sector accounting, enhancing understanding of how intangible HAs should be reported.